PARTISIPASI MASYARAKAT DALAM PEMANFAATAN DANA DESA DI DESA PITU - Richard Djiko; Remelia Dalensang (ipdn, 2021)
Public participation for development activities made by the government is a very important activity, so that the community must be involved, such as in planning, implementing, utilizing results to evaluating activities made by the government. The purpose of this study was to determine how the public participation in development activities in Pitu village. This research uses desciptive qualitative approach. Data collection techniques in this study use observation, interviews, and documentation. Data analysis in this study used the analytical method of Milles and Huberman, namely data reduction, data presentation and conclusion drawing. Based on the results of research in the field, it can be concluded that public participation in decision-making has not gone well, because the government in providing information to the community is not conveyed properly. Public participation in the implementation of development is still very tiny, such as participation in the form of contributing thoughts, materials and physically in development activities. In utilizing the results that have been made by the government, the people of Pitu Village are highly enthusiastic about it, but there are still some that are not in accordance with their needs. The community is more active in participating in giving criticism after there are development results to the village government through social media and others, but this form is not in the right place. Keywords: Public Participation, Development, Village Fund